The Impact of Domestic Public Debt and Budget Deficit on Aggregate Supply in Iraq - Al-Mamoori, Dr. Mahdi Khaleel Shadeed; Alaallah , Dr. Abduljasim Abbas; Al Dulaimi, Dr. Haidar Ali (International Journal of Accounting and Economics Studies, 2025)
public debt, the general budget deficit, and aggregate supply in the Iraqi economy—over the period 2004–2021, by employing the Vector ‎Error Correction Model (VECM), which is suitable for non-stationary, cointegrated time series. The structural imbalance in aggregate supply, driven by the high relative contribution of the oil sector, has significantly influenced changes across all economic sectors that constitute ‎the gross domestic product (GDP), as well as those linked through forward and backward linkages. Consequently, domestic public debt has ‎increased, accompanied by a limited sustainability of the budget deficit.‎ Furthermore, negotiations with the International Monetary Fund, the World Bank, and the Paris Club, in cooperation with international ‎financial and legal advisors and auditors, contributed to a substantial reduction in Iraq’s external debt—achieving an 80% write-off of the total ‎external public debt. This had a positive impact on the absolute values of GDP, the budget deficit, and the overall macroeconomic performance.‎ Econometric analysis confirms the existence of both long-run and short-run relationships among the study variables. These relationships ‎appear more pronounced in the direction from the budget deficit and aggregate supply to domestic public debt, as well as from domestic ‎public debt and aggregate supply toward the budget deficit within the Iraqi economy. Moreover, the temporal path of aggregate supply ‎closely mirrored the trajectories of both domestic public debt and the budget deficit throughout the period 2004–2021‎.